Методичні основи розробки інформаційної технології моделювання процесів стійкого розвитку комерційного банку в умовах ризику ліквідності - Кайдан, Л.І. (Економіко-математичне моделювання соціально-економічних систем, 2016)
The intelligent technology to model the process of the commercial bank’s sustainable development under conditions of the risk of liquidity is proposed. It is based on the program principal approach for the use of apparatus of probability automated modeling to support management decisions on basis of the internal bank automated information systems' modernization.